Multiwavelength Brillouin-erbium fiber laser incorporating stimulated brillouin scattering as mirror - Ajiya M.; Mahdi M.A.; Al-Mansoori M.H.; Hambalil N.A.M.A.; Gangl S.Y. (2023)
We demonstrate a method of generating a multiwavelength Brillouin/Erbium fiber laser in a ring cavity, with stimulated Brillouin scattering as a mirror. All Four generated Stokes lines have peak powers above 0 dBm with equal spacing of 10 GHz (0.08 nm) at 130 mW pump power from a 1480 nm laser diode. Our technique suppresses other potential modes to circulate in the laser cavity, thus the self-lasing modes are eliminated. The tuning range over 39 nm from 1527 nm to 1566 nm was successfully demonstrated, which is only limited by the amplification bandwidth of the erbium gain. 2009 SPIE.